Information security illuminated - Solomon, Michael G. (Jones and Bartlett Publishers, 2005)
A comprehensive survey of the most current and critical information security practices, Information Security Illuminated is an excellent introduction to the fundamental concepts and applications for students and professionals alike. Key security concepts are discussed with clear, accessible language and reinforced by a large number of scenario-based exercises and practical review questions. Readers are then able to apply their knowledge through hands-on experience with computer security-related tools. Coverage begins with the basics of computer security (CIA and DAD triads, risk analysis, etc.), and moves quickly through to important, real-world topics such as access control methodologies, security principles and practices, business continuity planning and disaster recovery, firewalls, incident handling, and much more. In addition to providing the requisite material for a complete course in information security practices, the book can be used as a self-study guide for many of the basic security certifications.